2023
DOI: 10.1007/s11214-022-00946-8
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Motions in the Solar Atmosphere

Abstract: Vortex flows, related to solar convective turbulent dynamics at granular scales and their interplay with magnetic fields within intergranular lanes, occur abundantly on the solar surface and in the atmosphere above. Their presence is revealed in high-resolution and high-cadence solar observations from the ground and from space and with state-of-the-art magnetoconvection simulations. Vortical flows exhibit complex characteristics and dynamics, excite a wide range of different waves, and couple different layers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 238 publications
(480 reference statements)
0
10
1
Order By: Relevance
“…Therefore, while the observational signature of magnetic tornadoes in the corona may be faint, they may be more frequently occurring phenomena than currently observed. For more information about vortices in the solar atmosphere, please refer to the review by Tziotziou et al (2023). A recent numerical simulation by Wedemeyer-Böhm et al (2012) demonstrated that magnetic tornadoes are capable of transporting sufficient energy to heat the quiet Sun corona.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, while the observational signature of magnetic tornadoes in the corona may be faint, they may be more frequently occurring phenomena than currently observed. For more information about vortices in the solar atmosphere, please refer to the review by Tziotziou et al (2023). A recent numerical simulation by Wedemeyer-Böhm et al (2012) demonstrated that magnetic tornadoes are capable of transporting sufficient energy to heat the quiet Sun corona.…”
Section: Introductionmentioning
confidence: 99%
“…The third task is to increase the capacity of the wind device due to the vertical pipe installed on the concentrator, provided by vertical traction. Similar works are related to the study of the solar vortex structure [22], which was developed at the Georgia Institute of Technology (Atlanta, USA). In russia, wind devices were created using the Darye rotor in the form of various modifications [23].…”
Section: Discussion Of the Results Of Studies Of The Efficiency Of A ...mentioning
confidence: 84%
“…The M-and K-vortices are different structures, as their centers and boundaries are localized at different positions and they appear and disappear at different time frames. This is clear when looking at Figure 18 from Tziotziou et al (2023), for example. Their coexistence leads to a structure defined as a magnetic tornado, described by Wedemeyer-Böhm et al (2012).…”
Section: Introductionmentioning
confidence: 87%
“…Flow or kinetic vortices (K-vortices), which are defined as vertical rotating columns of plasma flow (see, e.g., Silva et al 2020), are also believed to be an essential mechanism to create magnetic energy input to compensate for chromospheric losses (Shelyag et al 2012;Wedemeyer-Böhm et al 2012;Yadav et al 2021;Tziotziou et al 2023). In K-vortices, the vertical Poynting flux is still mainly created by work done by the horizontal plasma motion on the vertical magnetic field encompassed by the vortex tubes (Yadav et al 2021) and intensified around the vortex tube boundaries (Kitiashvili et al 2012).…”
Section: Introductionmentioning
confidence: 99%